Elections, political connections and cash holdings: Evidence from local assemblies - David Adeabah; Charles Andoh; Simplice Asongu; Isaac Akomea-Frimpong (African Governance and Development Institute (AGDI), 2021)
We examine the relationship between elections, political connections, and cash holdings in Ghanaian local assemblies. Using a panel dataset of 179local assemblies over a period 2012 to 2017, a panel regression and the generalized method of moments estimation techniques was employed for the analysis. We find that local assemblies hold less cash during election years, which suggests that election may be one of the potential factors to mitigate agency conflict in weak governance environment. Further, we demonstrate that local assemblies that have political connections hold less cash; however, political uncertainty makes these entities conducive to agency problems than their non-connected peers because they hold more cash. Additional analysis indicates that one year prior to elections, managerial conservatism kicks-in and leads managers to hold more cash in local assemblies that have political connections, which continues and becomes more pronounced in election years. Our results have implications for regulations on the cash management practices of local assemblies.
Keywords: 330; agency problem; cash holdings; generalized method of moments; panel regression; political connections